Chinese herbal medicine for postpartum constipation: a protocol of systematic review and meta-analysis. Issue 1 (15th January 2019) - Zhai, Jingbo; Li, Yan; Lin, Jingyi; Dong, Shuo; Si, Jinhua; Zhang, Junhua
Abstract : Introduction: Constipation is one of the most common gastrointestinal symptoms in postpartum mothers. The choice of treatments for postpartum constipation remains a challenging clinical problem. Chinese herbal medicine has become increasingly popular as an alternative therapy for constipation. This systematic review aims to evaluate the efficacy and safety of Chinese herbal medicine for postpartum constipation. Methods and analysis: We will search PubMed (1946 to present), EMBASE (1974 to present), Cochrane Central Register of Controlled Trials (all years), Web of Science (1900 to present), Chinese Biomedical Literatures Database (1978 to present), China National Knowledge Infrastructure (1979 to present) and WANFANG data (1998 to present) to identify any eligible study. No restriction will be put on the language, publication date or status of the study. The primary outcome will be the spontaneous bowel movement. Secondary outcomes will be stool consistency, quality of life, transit time, relief of constipation symptoms and adverse events. We will perform the meta-analysis when more than one trial examines the same intervention and outcomes with comparable methods in similar populations. If the heterogeneity is not significant statistically (p>0.10 or I 2 <50%), the fixed-effect model will be built to estimate the overall intervention effects. Otherwise, the random-effect model will be used to provide more conservative results. Ethics and dissemination: No ethical issues are foreseen because no primary data will be collected. The results will be published in a peer-reviewed scientific journal. PROSPERO registration number: CRD42018093741